2004
DOI: 10.1002/nvsm.245
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for lapse: the case of face‐to‐face donors

Abstract: INTRODUCTIONFace-to-face fundraising was adopted in the UK for the first time in 1997. It differs from traditional forms of street collection in that the solicitor is typically employed by an agency, rather than being a volunteer, and the donor is asked, not for a cash gift, but rather for a committed, regular gift deducted automatically each month from their bank account or credit card. The technique has grown enormously in popularity, recruiting many hundreds of thousands of new donors each year to both char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 6 publications
3
37
0
1
Order By: Relevance
“…College tuition and requests for donations from other charities compete with the annual campaign for resources. These reasons are consistent with those found in previous research (Khumawala, 1999;Sargeant and Jay, 2004).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…College tuition and requests for donations from other charities compete with the annual campaign for resources. These reasons are consistent with those found in previous research (Khumawala, 1999;Sargeant and Jay, 2004).…”
Section: Discussionsupporting
confidence: 94%
“…The findings of this study found evidence to support the findings of Sargeant and Jay (2004) concerning changes in financial status of givers. Although recent changes in household financial status were not measured, there was significant difference between the donor groups in financial status, measured as household income, and the amount of the gift.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of particular interest in the context of the current investigation are studies that focussed on donor lapse and retention. In this connection, Sargeant and Jay (2004) and Sargeant and Hudson (2008) highlighted the importance of post-donation service quality, especially in relation to communications with donors, as a determinant of whether subsequent donations would be made. Bendapudi et al's.…”
Section: Time To the Second Donationmentioning
confidence: 97%